2‐nm‐Thick NiCo LDH@NiSe Single‐Crystal Nanorods Grown on Ni Foam as Integrated Electrode with Enhanced Areal Capacity for Supercapacitors. Issue 6 (11th February 2020) - Lu, Chengxing; Yan, Yu; Zhai, Tengfei; Fan, Yuzun; Zhou, Wei
Abstract: It remains a great challenge to simultaneously guarantee the conductivity and high areal loading of active materials for integrated electrode of supercapacitors. Herein, we designed a hierarchical structure with cores of NiSe single‐crystal nanorods and sheaths of 2‐nm‐thick NiCo thin sheets grown on nickel foam (NiCo LDH@NiSe/NF) as integrated electrode. It reaches a high areal capacity of 1131 μAh cm −2 at a current density of 5 mA cm −2, which is 2.2 times of NiSe/NF (522 μAh cm −2 ) and 6.0 times of NiCo LDH/NF (189 μAh cm −2 ), superior to most reported integrated electrodes. The enhanced areal capacity can be ascribed to the high active material loading of 6.5 mg cm −2 (twice more than other reported values) and considerable conductivity of single‐crystal NiSe nanorods of 2630 S cm −1 . The fabricated hierarchical integrated electrode of NiCo LDH@NiSe/NF assembled with activated carbon shows a maximum energy density of 0.454 mWh cm −2 and a maximum power density of 80 mW cm −2 . This work presents supports of single‐crystal nanorods for thin LDH sheets to fabricate high‐density hierarchical structure for integrated electrode, which improves the conductivity and structural stability of active materials especially the LDHs, resulting in excellent electrochemical performance. It offers a promising approach to engineer and fabricate advanced supercapacitors with enhanced areal capacity. Abstract : A slim electrode : An integrated hierarchical electrode is fabricated using single‐crystal NiSe nanorods grown on nickel foam as scaffolding to support 2‐nm‐thick NiCo LDH nanosheets. Due to the high conductivity of single crystal NiSe, the presence of more active sites in few atomic layered LDH, as well as the construction of 3D hierarchical structure, the integrated electrode shows high areal capacity.